Remembered space : Memory and identity in Psalms 137-145 - Prinsloo, G.T.M. (Gert Thomas Marthinus) (University of Pretoria, 2020)
Dissertation (MA (Ancient Languages and Cultures))--University of Pretoria, 2020.